Passage, profit, protection and the challenge of participation - Loren B. Landau (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Accepting that successful 'development' is premised on a population's participation in a collective undertaking, we must understand urban residents'; interactions and ambitions. In African cities being transformed by geographic and social mobility, it is unclear what forms of inclusion, solidarity or mutual recognition are desired or possible among those who live there. This paper argues that the pursuit of three objectives - profit, protection and passage - shaping these cities' social formations in ways that limit the ability of official and non-official institutions to interweave popular aspirations - however temporarily - to promote a common and mutually beneficial future. The paper starts from the premise that the novelty of the emerging social forms within Africa's cities requires a willingness to induce: to build a conceptual vocabulary of belonging reflecting practices of those living in and moving through Africa's cities. Only after doing this will we have the building blocks for further debate. With this in mind, the paper works towards a pair of interrelated tasks. The first is to challenge three premises often informing discussions of mobility and urban politics: (i) the presence of a dominant host community or political order; (ii) that cities are destinations and not points of transit; and (iii) that state institutions are the primary source of exclusion and the most potent tool for fostering inclusion in a collective endeavour. Second, it considers one form of membership and inclusion that can emerge where the presumptions outlined above do not hold. In doing so, it points to a kind of 'tactical cosmopolitanism' a set of discourses and practices that can subvert ethnic or national chauvinism and restrictive migration or anti-urbanization policies and practices. Drawing primarily on examples from Johannesburg, it shows how migrants negotiate partial inclusion in transforming societies without becoming bounded by them. The paper ends by reflecting briefly on the challenges such tactics pose for generating a collective urban project.
Keywords: R0; R58; 330; migration; urbanization; African cities; social cohesion; integration; cosmopolitanism